MSS-1 ～ MSS-2 (The Japanese Journal of SURGICAL METABOLISM and NUTRITION, 2017)
Objectives Healthcare costs are a major and growing burden in many societies and primarily driven by non-communicable diseases, which are strongly linked to physical fitness. In this study, we explored whether physical fitness is associated with healthcare costs, and whether this association is causal. Methods We used data from the prospective Northern Finland Birth Cohort 1966 (NFBC1966, N=4,468, 55.5% women, age 46 years at baseline) for observational analysis. We measured cardiorespiratory fitness (CRF) via a step test and muscular fitness (MF) via handgrip strength and standardised both to minimal clinically important differences (MCID: one metabolic equivalent of task for CRF, 5 kg for MF). Healthcare costs, including primary and secondary care, and medication expenses, were obtained from national registers, log-transformed, and the analyses were conducted using linear regressions. As a robustness analysis, we conducted subgroup analyses of NFBC1966 participants with hypertension or overweight. To explore causal relations, we performed a two-sample Mendelian randomization (MR) analysis using genetic instruments from UK Biobank (CRF, MF) and FinnGen (healthcare costs). Results The mean annual total healthcare costs per NFBC1966 participant were €933 over the six-year follow-up. One MCID unit higher CRF was associated with 11% lower annual costs (P<0.001), and higher MF with 5% lower costs (P=0.001). Similar trends were observed in subgroups and across cost categories, although statistical significance was primarily reached for CRF. The direction of the MR estimates was consistent, but statistical significance varied across outcomes (point estimate β= -0.01 for CRF, P=0.877; β= -0.07, P=0.015 for MF). Conclusions Our findings partially support the hypothesis that better CRF and MF reduce healthcare costs.